Neuroprotective Effects of Sulforaphane on Cholinergic Neurons in Mice with Alzheimer’s Disease-Like Lesions - Rui Zhang (International Journal of Molecular Sciences, 2014)
Alzheimer’s disease (AD) is a common neurodegenerative disease in elderly individuals, and effective therapies are unavailable. This study was designed to investigate the neuroprotective effects of sulforaphane (an activator of NF-E2-related factor 2) on mice with AD-like lesions induced by combined administration of aluminum and d-galactose. Step-down-type passive avoidance tests showed sulforaphane ameliorated cognitive impairment in AD-like mice. Immunohistochemistry results indicated sulforaphane attenuated cholinergic neuron loss in the medial septal and hippocampal CA1 regions in AD-like mice. However, spectrophotometry revealed no significant difference in acetylcholine level or the activity of choline acetyltransferase or acetylcholinesterase in the cerebral cortex among groups of control and AD-like mice with and without sulforaphane treatment. Sulforaphane significantly increased the numbers of 5-bromo-2'-deoxyuridine-positive neurons in the subventricular and subgranular zones in AD-like mice which were significantly augmented compared with controls. Atomic absorption spectrometry revealed significantly lower aluminum levels in the brains of sulforaphane-treated AD-like mice than in those that did not receive sulforaphane treatment. In conclusion, sulforaphane ameliorates neurobehavioral deficits by reducing cholinergic neuron loss in the brains of AD-like mice, and the mechanism may be associated with neurogenesis and aluminum load reduction. These findings suggest that phytochemical sulforaphane has potential application in AD therapeutics.